Medical Rehabilitation and Occupational Therapy in Patients with Lesion of Plexus Brachialis - Vacheva D. (Sciendo, 2015)
Causes for plexus brachialis damage are versatile, and in some cases remain unknown, but mostly result from degenerative and inflammatory processes. Treatment of brachial plexus dysfunction is often conservative and is subject to a team of specialists - neurologists, traumatologists, rehabilitation physicians, kinesitherapists and occupational therapists. The objective of the research is to report the recovery of patients with lesion of plexus brachialis after a complex physiotherapy and rehabilitation treatment program that includes electrostimulation, remedial massage, kinesitherapy, electrotherapy and occupational therapy. A total of 159 patients, treated at the Clinic of Physical Therapy, University Hospital of Pleven, were included in the study. Improvement of measured indexes: pain assessment, centimetry, assessment of upper limb muscle weakness, dynamometry and functional test of activities of daily living, was registered in all patients under observation. In order to achieve good results in the rehabilitation of patients with injured plexus brachialis, timely diagnosis, good medication therapy and early start of complex physiotherapy and rehabilitation are of crucial importance, so that performance of daily living activities improves. The good results come slowly and with difficulties, but the quality of life of patients and the quality of labor performed by them, improves significantly.